Economic growth and poverty in Sumatra - Sari, Maulizar; Sartiyah, Aliasuddin (Opción, 2019)
This study aimed to analyze the effect of economic growth on poverty and income inequality in the region of Sumatra by using the ARDL panel model. The data used is the panel data from 2008 to 2017 and 120 districts/cities of 7 provinces in Sumatra with a total of 1200 samples. The results showed that in the short term on the GDP variables and GR no effect on poverty, but there is short-term relevance to the long-term. In conclusion, overall findings indicate that in the short term and long term, economic growth and income inequality affect poverty in Indonesia.